Evaluation of growth and production of the threatened giant river catfish, Sperata seenghala (Sykes) in polyculture with indigenous major carps - Rahman, Md. Aminur; Arshad, Aziz; Sarker, S. M. Nurul Amin Harmuj Ali (Academic Journals, 2011)
The giant river catfish locally named guizza, Sperata seenghala has significant cultural and economic importance but the fish is now considered as critically endangered due to environmental and manmade interventions in aquatic ecosystem. In order to conserve and rehabilitate this species, an experiment on polyculture of guizza with indigenous major carps was conducted in earthen ponds. Three treatments differing in species ratios and combinations of fish were employed with two replicates each. Treatment-1 (T1) was stocked with catla (Catla catla), rohu (Labeo rohita) and mrigal (Cirrhinus mrigala), treatment-2 (T2) with catla, rohu and guizza (S. seenghala), while treatment-3 (T3) with catla, rohu, mrigal and guizza. Guizza of T2 was introduced instead of mrigal in T1 and 50% of mrigal was replaced with guizza in T3. The stocking density of fish fingerlings in all the treatments was 7500 individual/ha. Fishes in the experimental ponds were fed with supplementary diet comprising of rice bran (50%), mustard oil cake (30%), fish meal (19%) and vitamin-mineral premix (1%). Physicochemical parameters and plankton populations were within the appropriate levels for aquaculture. Mean growth and survival of catla and rohu were significantly higher in T2 than in T3 and T1. Guizza in T2 showed higher performances than in T3, while those for mrigal were higher in T3 than T1 (p < 0.05). The total gross and net productions of fishes were higher in T3 than in T2 and T1 (p < 0.05). This trial is a successful attempt to culture the threatened guizza with major carps in earthen ponds, the findings of which would immensely be helpful towards the development of aquaculture and conservation of this important fish in captive condition.